Evaluation of the solid waste management at the Hospital I El Buen Samaritano of Bagua Grande - Amazonas, 2014. - Santisteban Salazar, Nelson César (2018)
To describe solid waste production and management at the Good Samaritan Hospital of Bagua Grande in theAmazonas region of Peru, as well as knowledge regarding solid waste management among hospital staff,between July and December of 2014. Descriptive, cross sectional observational study. Data was collectedthrough observations using structured guides and through interviews and a test applied to hospital staff. Theobservation guide and checklist used followed Peruvian Technical Standards of the Ministry of Health, theLeopold matrix for environmental impact assessment was used. We found a rate of waste generation of 2.56 kg/ bed / day; The waste management was poor; knowledge about biosafety was regular to excellent in medicalhospital staff, and poor among cleaning staff; The activities most harmful to the environment were infectiouswaste spills, incinerator use and discontinuous training, and the most affected environmental parameter wasoccupational health and safety. We conclude there is inadequate management of hospital waste because it doesnot comply with the national standards on sanitary waste management. Keywords: hospital solid waste; waste management, environmental health.